Analisis Desain Turbin Angin Horizontal 100 W di Pantai Koneng - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Michael Putra Humisar Tampubolon (JTM : JURNAL TEKNIK MESIN, 2026)
turbine at Pantai Koneng, Dumai, using NACA airfoils and QBlade simulation. The design compares three-blade and five-blade rotor configurations based on measured wind data, blade geometry, coefficient of power, tip speed ratio, rotational speed, and simulated power output. Primary wind data were obtained using a digital anemometer on 15-16 July 2023, while secondary data were taken from BMKG Pekanbaru and windPROSPECTING. The measured average wind speed at Pantai Koneng was 4.00 m/s, with a maximum hourly average of 6.00 m/s and a minimum of 3.00 m/s. The blade radius was set at 2 m with a taperless chord of 0.145 m and twelve blade segments using NACA 4424, NACA 4418, and NACA 4412 airfoils. QBlade results show that the three-blade configuration produces 230.793 W, coefficient of power 0.468, TSR 7, and rotational speed 200 rpm. The five-blade configuration produces 188.354 W, coefficient of power 0.382, TSR 5, and rotational speed 150 rpm. The three-blade rotor is therefore recommended because it provides higher simulated output and better suitability for the intended 100 W design target